2016
DOI: 10.1155/2016/7838290
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic Glucocorticoid-Rich Milieu and Liver Dysfunction

Abstract: We investigated the impact of chronic hypercorticosteronemia (due to neonatal monosodium L-glutamate, MSG, and treatment) on liver oxidative stress (OS), inflammation, and carbohydrate/lipid metabolism in adult male rats. We evaluated the peripheral concentrations of several metabolic and OS markers and insulin resistance indexes. In liver we assessed (a) OS (GSH and protein carbonyl groups) and inflammatory (IL-1b, TNFa, and PAI-1) biomarkers and (b) carbohydrate and lipid metabolisms. MSG rats displayed dege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…Chronic corticosteroids treatment has many adverse effects including hepatic dysfunction . The present study revealed liver function impairment with prednisolone treatment as previously reported, whereas MTK cotreatment attenuated this impairment in a dose‐dependent manner that was confirmed by histopathological findings.…”
Section: Discussionsupporting
confidence: 90%
“…Chronic corticosteroids treatment has many adverse effects including hepatic dysfunction . The present study revealed liver function impairment with prednisolone treatment as previously reported, whereas MTK cotreatment attenuated this impairment in a dose‐dependent manner that was confirmed by histopathological findings.…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, FAS gene expression was significantly upregulated with MSG treatment, which showed a marked downregulation with the Graviola treatment. This result was supported by [106] by finding that MSG rats are dyslipidemic, counteracting the stimulated liver lipogenic process by the high expression of their master regulator genes, Sterol regulatory element-binding transcription factor 1 (SREBP1c) target genes and fatty acid synthase (FAS) [107]. They showed that MSG rats developed an insulin-resistant state and increased oxidative stress, and severe liver injury characterized by inflammation and metabolic signs involved lipogenesis.…”
Section: Discussionmentioning
confidence: 86%
“…In this regard, synaptic plasticity, dopaminergic and serotonergic neurotransmission, and hypothalamic-pituitary-adrenal axis activity among many other neurological functions have been improved by n-3 PUFAs dietary supplementation [4244]. As is known, hypothalamic-pituitary-adrenal axis hyperactivity is an important hallmark in obesity, like that in MSG-obesity model [27, 45], and in many other human's metabolic disorders [4648]. …”
Section: Discussionmentioning
confidence: 99%